Pengaruh Variasi Serbuk batu Split sebagai aplikasi pemanfaatan Limbah Terhadap Karateristik Kuat Tekan Mortar: Pengaruh Variasi Serbuk batu Split sebagai aplikasi pemanfaatan Limbah Terhadap Karateristik Kuat Tekan Mortar - Trikopal, Iqbal; Yudid Jonathan; Zainuddin Muchtar; Kiky Rizky Amalia (PILAR, 2025)
This research aims to study the utilization of residual stone powder from stone crushers as a substitute for sand in mortar mixtures and to analyze the effect of stone dust variations on the compressive strength characteristics of mortar. The stone powder variations used are 0%, 22%, 26%, 30%, 34%, and 38%, with a total of 72 samples. Compressive strength testing was conducted at 14 and 28 days of age with immersion using PDAM water and swamp water. The results showed that the optimal substitution of stone powder is between 22% - 36%. The highest compressive strength was obtained at a 22% variation with a value of 14.21 MPa (PDAM water) and 13.71 MPa (swamp water). Conversely, the lowest compressive strength was recorded at a 38% variation with a value of 6.15 MPa (PDAM water) and 5.75 MPa (swamp water). Immersion using PDAM water (pH 6.34) produced higher compressive strength values compared to swamp water (pH 4.36), indicating that water pH affects the final results of the mortar. This study recommends the use of stone powder as a sand substitute in mortar production to achieve good quality.